A Novel Instrument for Endoscopic Ear Surgery With a Steerable Flexible Tip: A Pediatric Anatomical Validation Study. Issue 10 (December 2021) - Chayaopas, Nichtima; Swarup, Arushri; Eastwood, Kyle W.; Francis, Peter; Kahrs, Lueder A.; Maguire, Bryan; Drake, James; James, Adrian
Abstract : Hypothesis: This study compares the reaching ability of two classes of transcanal endoscopic ear surgery (TEES) instruments when operating on difficult to access anatomical targets; two novel instruments with steerable flexible tips (SFT-A and SFT-B) and suction capability are compared with standard commercially available tools. Background: TEES surgeons identified the need for a new surgical instrument that can enable accessibility of all areas visualized by the endoscope. This motivated the development of the two instrument prototypes. Methods: Six temporal bone models were 3D printed based on CT data from five cholesteatoma patients. Four anatomical targets were marked on each model. Using these targets, the reaching ability while using four standard TEES instruments were compared with the SFT-A and SFT-B prototypes by five surgeon participants. Results were analysed to compare success rates of contacting each target using each tool by fitting four Firth's logistic regression models. This calculated the statistically significant differences ( p < 0.05) in tool success rate. Results: Using SFT-A to contact the sinus tympani (100%) was significantly more successful than the Panetti suction dissector for atticus (PAT) (77%) and to contact the sinodural angle (0%) was less successful than the PAT (10%) and SFT-B (93%). Using SFT-B to contact the lateral semicircular canal (90%) was significantly more successful than all current tools and to contact the sinodural angle (93%) was significantly more successful than all tools. Conclusion: Using SFT-B enables enhanced accessibility of anatomical structures during TEES which may lead to less extensive bone removal to facilitate minimally invasive TEES. Abstract : Supplemental Digital Content is available in the text